Association of ABO blood group with respiratory disease hospitalization and severe outcomes: a retrospective cohort study in blood donors. (September 2022) - Su, Shu; Guo, Lingxia; Ma, Ting; Sun, Yang; Song, Aowei; Wang, Wenhua; Gu, Xiaoyun; Wu, Wenjie; Xie, Xinxin; Zhang, Leilei; Zhang, Lei; Yang, Jiangcun
Abstract: Objectives: Environmental, socioeconomic, and genetic factors all are associated with respiratory diseases. We aimed to investigate the association between the ABO blood group and the susceptibility to respiratory diseases. Methods: We constructed a retrospective cohort study of blood donors in Shaanxi, China between January 1, 2012, and December 31, 2018, to investigate the impacts of the ABO blood group on the risk of hospitalization due to respiratory diseases. Results: Of 1, 686, 263 enrolled participants (680, 788 females), 26, 597 were admitted to the hospital for respiratory diseases. Compared with blood group O, blood groups A, B, and AB all demonstrated a higher risk for diseases of the upper respiratory tract (International Classification of Diseases, Tenth Revision: J30–J39) (ARR (Adjusted relative risk) 1.139, 95% confidence interval [1.106–1.225]; 1.095 [1.019–1.177]; 1.178 [1.067–1.30], respectively). Conversely, blood group A was found to have a lower risk (0.86 [0.747–0.991]) for influenza (J09–J11) and blood group B had a lower risk for pneumonia (J12–J18) (0.911 [0.851–0.976]) than blood group O. The duration of hospitalization was significantly different across the blood groups in J09–J11 and J30–J39 ( P <0.05). Conclusion: The blood group appears to be a prognostic factor in differentiating the occurrence of specific respiratory diseases and duration.